2004
DOI: 10.1111/j.1423-0410.2004.00563.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of extended storage of whole blood before leucocyte depletion on coagulation factors in plasma

Abstract: Leucodepleted plasma originating from leucodepleted whole blood maintains a satisfactory level of coagulation factors, even after the storage of whole blood for 18 h at room temperature before filtration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
37
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 18 publications
10
37
2
Order By: Relevance
“…This was in agreement with Gosselin and Dwyre (2015) [17], who studied the effect of freezing on coagulation testing and found significant differences between fresh and frozen tested plasma for prothrombin time, APTT, factors V and VIII and ATIII. Contrary to our results, Kretzschmar et al [16], reported prolongation in APTT postfiltration with a polyurethane whole blood filter as well as a decrease in factor VIII:C; however, this was only significant after plasma storage at room temperature for 18 h preprocessing.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…This was in agreement with Gosselin and Dwyre (2015) [17], who studied the effect of freezing on coagulation testing and found significant differences between fresh and frozen tested plasma for prothrombin time, APTT, factors V and VIII and ATIII. Contrary to our results, Kretzschmar et al [16], reported prolongation in APTT postfiltration with a polyurethane whole blood filter as well as a decrease in factor VIII:C; however, this was only significant after plasma storage at room temperature for 18 h preprocessing.…”
Section: Discussioncontrasting
confidence: 86%
“…This study investigated the effect of two different methods of leucofiltration (filtration by inline whole blood polyester filters vs. automated apheresis machine) on the extrinsic and intrinsic pathway clotting factors in terms of prothrombin time, INR and PTT as well as on clotting factors V and VIII. There was a significantly prolonged prothrombin time in leucodepleted plasma samples, yet in our opinion, this might not be clinically significant as the absolute clotting time difference was 0.5 s. Contrary to our results, Kretzschmar et al [16] documented shorter prothrombin time postfiltration. They attributed this decrease to the release of factor V from platelets during storage or filtration process.…”
Section: Discussioncontrasting
confidence: 85%
“…Factor VIII dropped by 14% during the 8-hour ambient hold and dropped further to values that were about 26% lower than the initial values. Others confirmed these results for 18-hour-held whole blood [50] but also found a slight increase of C3a-desArg, indicative of complement activation with no clear cause; however, the authors suspected that the clinical relevance was low because it is quickly detoxified after release. Serrano et al [51] compared freshly processed PRPderived plasma clotting factors with overnight-held buffy coat-derived plasma and demonstrated that for an extended panel of clotting factors (14 in total), values for various plasma clotting factors from overnightheld whole blood fell between 84% and 130% of fresh.…”
Section: Effect Of Holding Time On the Quality Of Plasmasupporting
confidence: 50%
“…The authors commented that the single statistically significant difference could be considered to be due to chance and of no clinical relevance. Moreover, the half-life (T- 50) was not different at 26.2 ± 2.0 days for red cells from whole blood held for 8 hours vs 26.3 ± 2.6 days for those from whole blood held for 24 hours. The red cells were processed according to the PRP method, and white cells were not removed.…”
Section: Effect Of Holding Time Of Whole Blood On the Quality Of Red mentioning
confidence: 76%
See 1 more Smart Citation